Generic modeling of computer integrated manufacturing and assembly systems - De Souza, Robert (2008)
In this report, we present our research on an attempt in improving the conventional modeling systems. We propose a novel approach where dynamics, enhanced with intensive knowledge, are included in the stimulated model.